Fonte de m?ltiplos comprimentos de onda utilizando ?ptica n?o-linear, amplifica??o e realimenta??o ?ptica - Melo, Suzanne Assis de Souza (2014)
This work is focused on the development of multiwavelength sources using nonlinear optics, optical amplification and feedback. It is aimed to obtain optical frequency combs by increasing the efficiency of Multiple Four-Wave Mixing (MFWM) process. The work is based on analythical studies of the MFWM efficiency, as well as in numerical simulations using the piece of software VPI Transmission MakerTM and experiments in the laboratories WOCA (Wireless and Optical Convergent Access) from the National Institute of Telecommunications (Inatel) and Lasor from Research and Development Center in Telecomunications (CPqD). Numerical and experimental results demonstrate the efficiency of the proposed technique and its applications in optical communications, microwave photonics and ultrashort pulses generation.